2017
DOI: 10.1111/zph.12418
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in the parasite communities and genomic structure of urban rats in New York City

Abstract: Brown rats (Rattus norvegicus) are a globally distributed pest. Urban habitats can support large infestations of rats, posing a potential risk to public health from the parasites and pathogens they carry. Despite the potential influence of rodent-borne zoonotic diseases on human health, it is unclear how urban habitats affect the structure and transmission dynamics of ectoparasite and microbial communities (all referred to as "parasites" hereafter) among rat colonies. In this study, we use ecological data on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 60 publications
2
13
0
Order By: Relevance
“…Interestingly, limited movement was supported by an analysis of the ectoparasite communities of urban Norway rats. In this study, Angley et al (2018) found that rats located near each other geographically had more similar assemblages of ectoparasites than did rats located further apart. Because rat ectoparasites are transmitted among individuals via close contact, this implied that rats near each other came into contact with each other more frequently than those further apart.…”
Section: Site Fidelitymentioning
confidence: 51%
See 1 more Smart Citation
“…Interestingly, limited movement was supported by an analysis of the ectoparasite communities of urban Norway rats. In this study, Angley et al (2018) found that rats located near each other geographically had more similar assemblages of ectoparasites than did rats located further apart. Because rat ectoparasites are transmitted among individuals via close contact, this implied that rats near each other came into contact with each other more frequently than those further apart.…”
Section: Site Fidelitymentioning
confidence: 51%
“…Although such extended movements are infrequent [e.g., 19 of 230 black rats (8.2%) were classified as migrants in Sahel Niger (Berthier et al, 2016)], evidence of gene flow among Norway rat colonies from 1.5 to 3 km apart suggests that connectivity among populations is maintained by immigration amongst colonies (Gardner-Santana et al, 2009;Combs et al, 2018a). This dispersal may be nonrandom, whereby individuals move among similar habitat types (e.g., residential areas vs. mixed-used; Angley et al, 2018) and may also be facilitated anthropogenically, such as by commercial transport along road networks (Berthier et al, 2016).…”
Section: Dispersalmentioning
confidence: 99%
“…It is possible that urban rats benefit from sharing colonies with closely related individuals (e.g., territory defense, stable social structure), and may avoid some inbreeding tradeoffs by having relatively accelerated reproductive life cycles. One benefit may be less diverse parasite and pathogen communities harbored by isolated rats, and dispersal and culling can disrupt these relatively insular colonies (Angley et al, 2018;Lee et al, 2018;Minter et al, 2019).…”
Section: Increasing Relatedness and Fitness Consequencesmentioning
confidence: 99%
“…The current study is part of a multi-disciplinary effort to reduce the risk of leptospirosis for Pau da Lima residents, and a primary strategy is to reduce the population of Norway rats that serve as reservoirs of this bacterial pathogen (Ko et al, 1999;Costa et al, 2014;Richardson et al, 2017). Cities around the world are focused on reducing rat populations for reasons related to public health, quality of life, and protection of infrastructure (Bonnefoy et al, 2008;de Masi et al, 2009;Angley et al, 2018). The lethal control campaigns typically implemented are often successful at reducing the number of rats in the targeted areas yet are generally followed by a period of rapid population increase-the "boomerang effect" (Smith, 1963;de Masi et al, 2009).…”
Section: Implications For Urban Rat Managementmentioning
confidence: 99%
“…Despite their close proximity with humans, the biology and ecology of urban rats have been understudied (Himsworth et al 2013 ). If bacterial and viral organisms carried by rats know nowadays an increasing scientific interest (particularly if they are zoonotic) (Himsworth et al 2013 ; Desvars-Larrive et al 2017 ; Angley et al 2018 ; Strand and Lundkvist 2019 ), studies on the helminth fauna of urban rats remain scarce. Helminths can modify wildlife host population dynamics (Hudson et al 1998 ; Albon et al 2002 ), communities (Mouritsen and Poulin 2002 ) and health status (Tompkins et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%